A Comprehensive Review on Floating Drug Delivery System (FDDS) - Bhosale, Aishwarya Rajendra; Shinde, Jitendra V; Chavan, Rajashree S. (Journal of Drug Delivery and Therapeutics, 2020)
The main goal of any drug delivery system is to achieve desired concentration of the drug in blood or tissue, which is therapeutically effective and non-toxic for a prolonged period. Current pharmaceutical scenario focuses on the formulation of floating drug delivery system (FDDS). FDDS are low density systems that float over the gastric contents and remain buoyant in the stomach for a prolonged period of time without affecting the gastric emptying rate. The aim of writing this review is to compile the current literature with special focus on the principal mechanism of floatation to attain gastric retention. Effervescent FDDS release CO2 gas, thus reduce the density of the system and remain buoyant in the stomach for a prolonged period of time and released the drug slowly at a desired rate so it can be used to prolong the gastric residence time in order to improve the bioavailability of drug. The review briefly describes the mechanism, types of floating system, advantages, limitation, factors affecting floating system, drug candidates suitable for floating, evaluation parameters and application of the system. These systems are useful to several problems encountered during the development of a pharmaceutical dosage form and the future potential of FDDS. Keywords: Floating drug delivery system, Absorption Window, Effervescent system, floating lag time.